2020
DOI: 10.33314/jnhrc.v18i2.2658
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice of healthcare workers Towards Coronavirus Disease 2019 (COVID-19) Pandemic

Abstract: Background: The emergence of SARS-CoV 2 pandemic is the greatest public health concern of the century. Healthcare workers are the front liners of pandemic management. Their knowledge, attitudes and practices can influence the outcome of pandemic. The study aims to determine the knowledge, attitude and practices among healthcare workers.Methods: Knowledge, attitude and practice related questionnaire based online survey through Google forms was conducted from Healthcare workers, following ethical approval from N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 0 publications
3
10
0
Order By: Relevance
“…Regarding the isolation period of COVID-19, majority of the participants, 70.7% (282) were well known about it and 82.2% (328) had correct knowledge about prevention from COVID-19. This finding was consistent with a recent study done in Nepal [21]. Remarkably, all 100% of the respondents were well known about the fact that antibiotic was not the first line treatment of COVID-19.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Regarding the isolation period of COVID-19, majority of the participants, 70.7% (282) were well known about it and 82.2% (328) had correct knowledge about prevention from COVID-19. This finding was consistent with a recent study done in Nepal [21]. Remarkably, all 100% of the respondents were well known about the fact that antibiotic was not the first line treatment of COVID-19.…”
Section: Discussionsupporting
confidence: 92%
“…The logistic regression (forward stepwise) also revealed several factors being associated with the knowledge and attitude of the HCW's. Among then some were found matching with various studies conducted at national/ international level [17,[28][29][30] whereas some were found to contradict with the various study findings [21][22][23][24].…”
Section: Discussionmentioning
confidence: 73%
“…Regarding the isolation period of COVID-19, majority of the participants, 70.7% (282) were well known about it and 82.2% (328) had correct knowledge about prevention from COVID-19. This nding was consistent with a recent study done in Nepal [25]. Remarkably, all 100% of the respondents were well known about the fact that antibiotic was not the rst line treatment of COVID-19.…”
Section: Discussionsupporting
confidence: 91%
“…The logistic regression (forward stepwise) also revealed several factors being associated with the knowledge and attitude of the HCW's. among then some were found matching with various studies conducted at national/ international level [19,20,21], whereas some were found to contradict with the various study ndings [25][26][27][28] .…”
Section: Discussionmentioning
confidence: 66%
“…This moderate level of acceptance may be attributable to several reasons, e.g. inadequate knowledge among HCWs regarding COVID-19 [37,38], negative attitude towards the disease [37,39], and feelings of fear and anxiety during the COVID-19 pandemic [4043]. Also, concerns raised for COVID-19 vaccination are related with inadequate knowledge about such new vaccines regarding the long term side effects, effectiveness, efficacy etc.…”
Section: Discussionmentioning
confidence: 99%